Specific principles in the training of winter sports - Müller, E.; Lindinger, S.; Raschner, C.; Schwameder, H. (Book of abstracts of the 6th annual congress of the European College of Sport Science, 15th congress of the German Society of Sport Science. Cologne, 24-28 July 2001, 2001)
Verfasser berichten über die Zusammenarbeit des Instituts für Sportwissenschaften Salzburg und des Österreichischen Skiverbandes über die sportwissenschaftliche Betreuung der österreichischen Elite-Wintersportler.